2023
DOI: 10.1002/jha2.750
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haematological characteristics of 38 individuals with Hb G‐Makassar in Malaysia

Ezalia Esa,
Ahmad Sabry Mohamad,
Roszymah Hamzah
et al.

Abstract: Haemoglobin (Hb) G‐Makassar is a rare Hb variant. It presents a diagnostic challenge as it imitates sickle Hb (Hb S) in standard electrophoresis and high‐performance liquid chromatography assays requiring DNA analysis to confirm diagnosis. Both have point mutations in codon 6, exon 1 in the β‐globin (HBB) gene with different pathogenicities. This study describes the clinical phenotype, haematology and genotype of Hb G‐Makassar. Clinical and laboratory data of 38 cases of Hb G‐Makassar over 8 years were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(49 reference statements)
2
2
0
Order By: Relevance
“…Thus, molecular testing is essential for differential diagnosis. Furthermore, we reported two cases of Hb G-Makassar with Hb E, presenting mild clinical phenotypes similar to that in a previous report 39 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, molecular testing is essential for differential diagnosis. Furthermore, we reported two cases of Hb G-Makassar with Hb E, presenting mild clinical phenotypes similar to that in a previous report 39 .…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, Hb C is predominantly observed in southern Thailand, where malaria is endemic. Moreover, Hb G-Makassar is frequently observed in the southern population, similar to that in the Malaysian population 39 . Hb G-Makassar comigrated at the same retention time as that for Hb S, as determined using the CE technique.…”
Section: Discussionsupporting
confidence: 51%
“…18,19 Recently, a larger study involving individuals with heterozygous HbG-Makassar/beta thalassemia in Malaysia indicated that the HbG-Makassar behaves as a benign hemoglobin variant. 20 An HbGG individual was reported to have normal red cell indices and was also pregnant at the time of the report. 21 In a more recent study, the conversion of HbS to HbG-Makassar through base editing in a SCD mouse model showed the promising potential of this gene editing approach to correct the pathophysiology associated with sickle cell disease.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation spectrum of thalassaemia is unique, with some diversity and peculiarity according to specific geographical location and distinctive ethnic groups [19,20]. In Malaysia, few alpha and beta variants have been reported as unique among Malays, namely α2 Codon 141 (CGT>CCT) Hb Singapore NG_000006.1:g.34459G>C, [20] and Codon 6 [GAG>GCG] Hb G-Makassar (NG_000007.3:g.70614A>C) [21]. In 2019, Malaysian Thalassaemia Registry reported a total of 8178 registered thalassaemia patients, of which majority of them suffered from HbE/β-thal; followed by β-thal major (β-TM); Hb H disease; β-thal intermedia (β-TI); and others, with the percentage of 35.19%, 32.66%, 19.48%, 9.02%, and 3.64%, respectively [22,23].…”
Section: Introductionmentioning
confidence: 99%